Culture and power in traditional Siamese government - Englehart, Neil A., 1964- (Southeast Asia Program series ;, 2001)
A broad reevaluation of Siam's political culture as it existed prior to King Chulalongkorn's administrative reforms in the nineteenth century. Englehart offers evidence to show that traditional Siamese government functioned more effectively and rationally than most scholars have acknowledged.